Rotator cuff muscle degeneration and tear severity related to myogenic, adipogenic, and atrophy genes in human muscle. Issue 12 (2nd June 2017) - Shah, Shivam A.; Kormpakis, Ioannis; Cavinatto, Leonardo; Killian, Megan L.; Thomopoulos, Stavros; Galatz, Leesa M.
ABSTRACT: Large rotator cuff tear size and advanced muscle degeneration can affect reparability of tears and compromise tendon healing. Clinicians often rely on direct measures of rotator cuff tear size and muscle degeneration from magnetic resonance imaging (MRI) to determine whether the rotator cuff tear is repairable. The objective of this study was to identify the relationship between gene expression changes in rotator cuff muscle degeneration to standard data available to clinicians. Radiographic assessment of preoperative rotator cuff tear severity was completed for 25 patients with varying magnitudes of rotator cuff tears. Tear width and retraction were measured using MRI, and Goutallier grade, tangent (tan) sign, and Thomazeau grade were determined. Expression of myogenic‐, adipogenic‐, atrophy‐, and metabolism‐related genes in biopsied muscles were correlated with tear width, tear retraction, Goutallier grade, tan sign, and Thomazeau grade. Tear width positively correlated with Goutallier grade in both the supraspinatus ( r = 0.73) and infraspinatus ( r = 0.77), along with tan sign ( r = 0.71) and Thomazeau grade ( r = 0.68). Decreased myogenesis (Myf5), increased adipogenesis (CEBPα, Lep, Wnt10b), and decreased metabolism (PPARα) correlated with radiographic assessments. Gene expression changes suggest that rotator cuff tears lead to a dramatic molecular response in an attempt to maintain normal muscle tissue, increase adipogenesis, and decrease metabolism. Fat accumulation and muscle atrophy appear to stem from endogenous changes rather than from changes mediated by infiltrating cells. Results suggest that chronic unloading of muscle, induced by rotator cuff tear, disrupts muscle homeostasis. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2808–2814, 2017.